2019
DOI: 10.1155/2019/9650184
|View full text |Cite
|
Sign up to set email alerts
|

Novel SUFU Frameshift Variant Leading to Meningioma in Three Generations in a Family with Gorlin Syndrome

Abstract: Gorlin syndrome is mainly caused by pathogenic germline variants in the tumour suppressor genes PTCH1 and SUFU, both regulatory genes in the hedgehog pathway. However, the phenotypes of patients with PTCH1 and SUFU pathogenic variants seem to differ. We present a family with a frameshift variant in the SUFU gene c.954del, p.Asn319Thrfs∗42 leading to meningiomas and multiple basal cell-carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Localization of SUFU variants associated in previous studies with Joubert syndrome are indicated in green and blue; variants associated with Gorlin–Goltz syndrome are marked in red. 19 , 22 , 27 , 28 . …”
Section: Resultsmentioning
confidence: 99%
“…Localization of SUFU variants associated in previous studies with Joubert syndrome are indicated in green and blue; variants associated with Gorlin–Goltz syndrome are marked in red. 19 , 22 , 27 , 28 . …”
Section: Resultsmentioning
confidence: 99%
“…The risk of BCC in adult patients with germline SUFU mutations has not been estimated yet. Several SUFU PV carriers identified in GS cohorts have been diagnosed with multiple BCC [12][13][14][15], but most SUFU PVs were identified in infants treated for a medulloblastoma who were young at the time of clinical report and therefore their risk of BCC in adulthood cannot be assessed. In their relatives, the risk of BCC in adults is much lower than in classical GS related to PTCH1 PVs [6] suggesting that the risk of BCC in SUFU PV carriers is much lower than in PTCH1 PV carriers.…”
Section: Basal Cell Carcinoma (Bcc)mentioning
confidence: 99%
“…Indeed, in the Manchester cohort, the incidence of meningiomas was much higher in SUFU PV carriers (4/9) than in patients with a PTCH1 PV (2/126). Meningiomas have also been described, mostly as case reports, in patients with SUFU variants, either as the first brain tumor [ 12 , 14 , 25 ] or, more frequently, after irradiation for a medulloblastoma [ 6 , 13 , 26 , 27 ]. Most de novo meningiomas described so far occurred after the age of 40, whereas they occurred earlier in patients previously treated for a medulloblastoma.…”
Section: Genetic Associationsmentioning
confidence: 99%
See 1 more Smart Citation
“…From our experience, a clear distinction between a definite molar tooth sign and a milder hindbrain malformation as described here is occasionally challenging, even with a technically optimal MRI investigation. 19,22,27,28 .…”
Section: Discussionmentioning
confidence: 99%